TYPES OF FAMILIES OF JOINT FORCES OPERATION PARTICIPANTS IN THE EAST OF UKRAINE AND PECULIARITIES OF SOCIAL WORK WITH THEM - Dulia, Alina; Liakh, Tetiana; Veretenko, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Carrying out military actions in the East of Ukraine, Joint Forces Operations, lead to physical and psychological traumatization of military personnel, complications in their socialization into a peaceful society, deterioration of interaction between family members of participants of the Joint Forces Operation and family dysfunction. The purpose of this article is to classify types of families involved in the Joint Forces Operation and determine their specific problems and needs. Based on the survey of families and specialists of state and private organizations, providing social support for this category of recipients of services, classification of types of families participating the Joint Forces Operation (family members, where one of its members is now in a combat zone; families, where one of its members returned from the combat zone; families, who are divorced: before departure to the combat zone, during a stay in a combat zone, after returning from the combat zone; families where one member is war-disabled; the families of the deceased ones) was made. The characteristic of each of the certain types of families allowed choosing the most effective forms of work with the families of the Joint Forces Operation participants.